Discounted Payback and Time to Breakeven Are Two Different Measures - Ng, Chee (Journal of Applied Business and Economics, 2023)
The capital budgeting chapter teaches discounted payback as a corollary to net present value. Time-to-breakeven is taught in the time-value-money chapter which normally precedes the capital budgeting chapter. Due to myriad reasons, there are growing calls to simplify the curriculum by dropping the capital budgeting chapter as a requirement for non-finance majors to spend more time perfecting the delivery of the time-value-money chapter, which is a significant challenge to many students. This manuscript illustrates such calls are misplaced because the capital budgeting chapter is an essential chapter whose curricular contents include the discounted payback which is different and distinct from the time-to-breakeven taught in the time-value-money chapter.